2019
DOI: 10.21873/anticanres.13710
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Relative Dose Intensity of Early-phase Lenvatinib Treatment on Therapeutic Response in Hepatocellular Carcinoma

Abstract: Background: Factors associated with response to lenvatinib have not been clarified in patients with hepatocellular carcinoma (HCC). Patients and Methods: This study retrospectively analyzed 50 patients treated with lenvatinib as first-line therapy between March 2018 and March 2019. Patients were divided into two groups by the Modified Response Evaluation Criteria in Solid Tumours (mRECIST) (responders and non-responders, whose best overall responses were complete (CR)/partial response (PR) and stable (SD)/prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
58
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(71 citation statements)
references
References 27 publications
11
58
2
Order By: Relevance
“…RDI was found to be significantly related to complete or partial response. Recently, the therapeutic effects of LEN at particular dosages have been reported [23,24]. Those works concluded that achieving a sufficient RDI was crucial to therapeutic efficacy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RDI was found to be significantly related to complete or partial response. Recently, the therapeutic effects of LEN at particular dosages have been reported [23,24]. Those works concluded that achieving a sufficient RDI was crucial to therapeutic efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…If an AE occurred, the dose was reduced or the treatment was temporarily interrupted until the symptoms improved to grade 1 or 2, based on the guidelines from Eisai Co., Ltd. The relative dose intensity (RDI) was calculated by dividing the actual dose by the ideal dose for the first 30 days of treatment [23,24].…”
Section: Protocolmentioning
confidence: 99%
“…It is well accepted that RDI is a useful indicator for evaluating the feasibility of pharmacotherapy, especially anticancer drug treatment [7]. The importance of RDI has also been reported in molecular targeted therapy for HCC [12,16]. Wang et al investigated the significance of RDI for the first month (1M-RDI) of regorafenib in patients with HCC, which reported that patients with 1M-RDI ≥50% showed significantly longer OS and PFS than patients with 1M-RDI <50% [12].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a post-hoc analysis of the REFLECT trial reported that the objective response based on the mRECIST was an independent predictor of OS [14]. In addition, we previously reported that 95.5% of responders achieved an objective response at the first evaluation after LEN initiation [15]. Therefore, we hypothesized that ETS may also reflect the treatment outcome of patients with HCC.…”
Section: Introductionmentioning
confidence: 95%